PENGARUH CITRA MEREK, PERSEPSI HARGA DAN INTENSITAS PROMOSI TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN (Studi Empiris Pada Konsumen Produk Uniqlo Mahasiswa Universitas Diponegoro) - Putri, Meylisa Eka; Hidayati, Retno (Diponegoro Journal of Management, 2023)
ABSTRACT In the current era of globalization, the fashion business is one type of business that is quite popular among consumers after the food business. Uniqlo is an alternative fashion choice for consumers. However, there are still many consumers who are confused when making purchasing decisions regarding fashion products, especially Uniqlo. Paying attention to brand image, price perception and promotional intensity could be a strategic solution for a company to convince consumers to decide to buy a product. This research aims to analyze the influence of brand image, price perception and promotional intensity on purchasing decisions among Uniqlo product consumers, Diponegoro University students. The population in this study were Uniqlo product consumers, Diponegoro University students. Data was obtained through questionnaires from a sample of 142 people using a non-profitability, purposive sampling approach. Then, the analysis technique uses multiple linear regression. The results of the research show that brand image, price perception, and promotional intensity have a significant positive effect on consumer purchasing decisions for Uniqlo products among Diponegoro University students. In this way, the company must further improve its brand image, price perception and promotional intensity to improve Uniqlo consumer decision making.